Research Progress on the Whitening of Angelica Dahurica - Zhong, Linrui (International Journal of Public Health and Medical Research, 2025)
This paper mainly reviews the application status and research progress of Angelica dahurica in the field of whitening in recent years, analyzes its active ingredients, mechanism of action, and existing problems, and provides a theoretical basis for the subsequent development of natural whitening products. Through literature review and summary. The extensive use of Angelica dahurica in both ancient and modern times confirms that its whitening and skin care effects are certain. However, there are still issues such as unclear mechanisms related to its whitening active ingredients and photosensitive coumarin components, and the photosensitivity of coumarin components limits their application in cosmetics. The idea of using natural active ingredients for skin care is becoming increasingly popular, and the development, validation, and application of natural whitening active ingredients will be the future direction of cosmetics. This article provides relevant references for the further development and application of Angelica dahurica in the field of whitening.